KOMPATIBILITAS BATANG BAWAH NANGKA TAHAN KERING DENGAN ENTRIS NANGKA ASAL SULAWESI TENGAH DENGAN CARA SAMBUNG PUCUK - Yohanis Tambing; Enny Adelina; Tati Budiarti; Endang Murniati (Universitas Tadulako, 2008)
The research on vegetative breeding of jack fruit has been conducted through grafting method, aiming at finding out the compatibility of lower cultivar resisting to drought stress with the jack fruit entries of pre-eminent varieties originally from central Sulawesi. Generally, the results of the research indicated that all entries except those grafted with the root stock BK-3 and TL-5 could only survive for 2 weeks leaving only their dead scions. The latter appeared to be compatible with the Palupi entries as they were still able to live and grew until this research ended